Target setting in agriculture - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This presentation was given by Lini Wollenberg, CCAFS Low Emissions Development Flagship, at a workshop on ICF transparency and long-term strategies for LED on September 28th, 2020.